Trace amine-associated receptor 1 agonist reduces aggression in brain serotonin-deficient tryptophan hydroxylase 2 knockout rats - Zhukov, Ilya S.; Alnefeesi, Yazen; Krotova, Natalya A.; Nemets, Vsevolod V.; Demin, Konstantin A.; Karpenko, Marina N.; Budygin, Evgeny A.; Kanov, Evgeny V.; Kalueff, Allan V.; Shabanov, Petr D.; Bader, Michael; Alenina, Natalia; et al. (Frontiers in Psychiatry, 2024)
IntroductionAggression and self-harm disproportionately occur in youths preoccupied with social status tracking. These pathological conditions are linked to a serotonin (5-HT) deficit in the brain. Ablation of 5-HT biosynthesis by tryptophan hydroxylase 2 knockout (TPH2-KO) increases aggression in rodents. Remarkably, deletion of the trace amine-associated receptor 1 (TAAR1) results in the same consequences. Unlike the nuanced dynamics of social status cues in young people, the social ranks of rats mainly advance when they dominate larger opponents in combat.MethodsThis study explored whether the potent TAAR1 agonist RO5263397 reduces aggression caused by 5-HT depletion, and whether social rank advancement motivates this aggression. The resident-intruder paradigm was applied with larger and smaller intruders to evaluate whether social rank advancement motivates aggressive behaviors in TPH2-KO rats.ResultsWhen a smaller intruder was introduced, 5-HT-deficient rats did not differ from wild type littermates. However, when the intruders were larger, the mutants extended their aggressive efforts, refusing to submit. Importantly, RO5263397 selectively abolished this abnormal form of aggression in TPH2-KO rats.DiscussionResults supported social rank advancement as the main incentive. These data also suggest that TAAR1 is a promising target for the development of new treatments for aggression; independent data also support this conclusion.